Crucial role for pathology residents in laboratory self-inspection, a single Institute's experience - Ted Farzaneh; Beverly Wang; Nancy Clark; Carol Eade-Viele; Joyce Kelner; Jennifer Rodgers; Geoffrey Sempa; Neil Detweiler; Tara Kasmarek; Thomas Lee; Xiaohui Zhao; Edwin S. Monuki; et al. (Practical Laboratory Medicine, 2019)
Background: Training in patient safety, quality, and management is a key component of Graduate Medical Education (GME) training in all specialties. However, residency programs, especially Pathology programs, often find it challenging to create strong learning opportunities in these areas. Objectives: Focused quality assurance (QA) projects are one approach to teach and engage trainees in these key areas. Residents have been historically involved in different QA projects in our department but mainly in small secondary roles. Leading a large QA project that can enhance residents’ management skills and improve clinical operations in our laboratory was the main objective of our project. Description: A new process for laboratory self-inspection led by residents was implemented that simulates the exact process of a formal outside College of American Pathologists (CAP) inspection. We aim to prove that resident-led QA activities not only have profound educational benefit but can also result in significant performance and operational improvement. Results: For this paper, we focus on the Histology laboratory since the ramifications from the self-inspection process during a three year period were profound leading to change in management, workflow changes, and notable improvement in staff morale. Conclusion: The self-inspection process exposed the residents to operational issues and corrective actions that provided them the opportunity to take a more active role in laboratory management and helped prepare them for post-graduation challenges. It also helped the department identify and rectify many operational issues, confirmed by the enumeration of CAP deficiencies and significant improvement of staff morale. Keywords: Pathology residents, College of American pathologists (CAP), Self-inspection, Histology, Quality assurance (QA)